2015
DOI: 10.15244/pjoes/35283
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-Scale Investigation of Biogas Treatment by Removal of Hydrogen Sulfide and Carbon Dioxide

Abstract: The use of organic residues and waste for production of biogas as an energy source is a viable option for waste management and reduction of greenhouse gas emissions. However, before any eventual utilization of biogas, hydrogen sulfide (H 2 S) and carbon dioxide (CO 2 ) must be removed since those contaminants are highly undesirable in combustion systems. This work deals with the construction and examination of a laboratoryscale, low-cost test stand for quick evaluation of the existing and new methods for H 2 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…Amine solution is widely used to absorbed CO 2 and there is little or no methane losses (0.1-1.2%), with methane recovery greater than 99% because the chemical solvent reacted selectively with CO 2 . Although some reports [7,8,16,20] reported methane losses up to 4% due to CH 4 dissolution in alkanolamine. It also operated like water scrubbing countercurrent flow configuration, and H 2 S should be treated prior to chemical scrubbing because of amine poisoning (Fig.…”
Section: Chemical Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amine solution is widely used to absorbed CO 2 and there is little or no methane losses (0.1-1.2%), with methane recovery greater than 99% because the chemical solvent reacted selectively with CO 2 . Although some reports [7,8,16,20] reported methane losses up to 4% due to CH 4 dissolution in alkanolamine. It also operated like water scrubbing countercurrent flow configuration, and H 2 S should be treated prior to chemical scrubbing because of amine poisoning (Fig.…”
Section: Chemical Absorptionmentioning
confidence: 99%
“…This is the same way as water/glycol scrubbing for biogas-liquid mass transfer principles, but chemical reaction takes place between the solvent and the absorbed substances. It relies on CO 2 reactive absorbents such as alkanol amines (mono ethanol amine (MEA)) or di-methyl ethanol amine (DMEA), and alkali aqueous solutions such as KOH, K 2 CO 3 , NaOH, Fe(OH) 3 , FeCl 2 [20]. The unit consists of a packed bed (random or structural) coupled with desorption unit equipped with reboiler to simplify process configuration, with no risk of biomass growth as result of high pH of the amine solutions [4].…”
Section: Chemical Absorptionmentioning
confidence: 99%
“…These results are in agreement with previous studies (Chung et al, 2006; Ho et al, 2013; Horikawa et al, 2004; Lin et al, 2013), which removed H 2 S by a combined chemical–biological solution, showing that H 2 S removal efficiency increased with increasing retention time. Others have found that H 2 S removal efficiency increased with increasing retention time through increasing bed height of bog iron ore (30, 53, and 80 mm height) at the same gas flow rate (Lasocki et al, 2015) or with decreasing biogas flow rates (from 60–80% at 50 L min −1 to 25–60% at 140 L min −1 ) (Lien et al, 2014). Pagella et al (1996) found that the H 2 S removal efficiency can be enhanced through either reducing gas flow rates or increasing the soil volume.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with the studies of Chung et al (2006), who concluded that more than 99.5% of H 2 S is removed in the first 10 h of feeding by chemical adsorption. Lasocki et al (2015) indicated that using bog iron ore and activated carbon as H 2 S adsorption beds in filters also reduced almost 100% of H 2 S in a 30-min exposure period. Rogers and Whitehead (1998) showed that 2500 mg L −1 H 2 S concentration in raw gas was removed to below 1 mg L −1 by three different filtration stages, including an iron chelate solution, a dry iron oxide box, and an activated carbon filter.…”
Section: Effect Of Gas Flow Ratesmentioning
confidence: 99%
“…Additionally small amount of ammonia (NH 3 ), hydrogen sulfide (H 2 S), nitrogen (N 2 ), oxygen (O 2 ), carbon monoxide (CO), water (H 2 O), siloxanes and halogenated volatile organic compounds (VOCs) are present as impurities in biogas [2; 5-8]. Table 1 shows the chemical composition of raw biogas from different sources [7].…”
Section: Introductionmentioning
confidence: 99%